2012
DOI: 10.18632/oncotarget.634
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of growth hormone-releasing hormone suppress in vivo tumor growth and gene expression in triple negative breast cancers

Abstract: This study evaluated the effects of a modern antagonistic analog of GHRH on tumor growth and on expression of inflammatory cytokine genes in two models of human triple negative breast cancers (TNBC). The TNBC subtype is refractory to the treatment options available for other hormone-independent breast cancers. Inflammatory cytokines play a major role in the cellular signaling associated with breast cancer pathogenesis and enhance epithelial-mesenchymal transitions (EMT), drug resistance, and metastatic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…Although the presence of GHRH-R has been previously identified in multiple types of human cancers (11)(12)(13)(14)(15)(16)(17)(18)(19), the clinical importance of GHRH-R in the tumorigenic progression and patient outcome was unappreciated prior to this study. In this study, by analyzing multiple cohorts of GC patients of different races, we defined the heretofore undocumented associations between GHRH-R and poor survival of human GC.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the presence of GHRH-R has been previously identified in multiple types of human cancers (11)(12)(13)(14)(15)(16)(17)(18)(19), the clinical importance of GHRH-R in the tumorigenic progression and patient outcome was unappreciated prior to this study. In this study, by analyzing multiple cohorts of GC patients of different races, we defined the heretofore undocumented associations between GHRH-R and poor survival of human GC.…”
Section: Discussionmentioning
confidence: 96%
“…( [11][12][13][14][15][16][17][18][19]. The GHRH/GHRH-R pathway is considered a growth factor-signaling pathway in these cancers and may modulate the activities of multiple intracellular pathways (11)(12)(13).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Anti-inflammatory effects for GHRH antagonists were also demonstrated in experimental models of cancer and ocular inflammation (39,40).…”
Section: Significancementioning
confidence: 97%
“…22 We have shown previously that GHRH antagonists inhibit the growth of diverse human tumors xenografted into nude mice. [23][24][25][26][27][28][29][30] Many of these published studies reported the effects of early-stage GHRH antagonists that were later considered unsuitable for clinical development due to limited stability or low potency. In our initial studies with melanomas, for example, early GHRH antagonists MZ-5-156, MZ-7-138 and JMR-132 were shown to inhibit growth of MRI-H187, MRI-H255 and A375 human melanoma cell lines xenografted into nude mice.…”
Section: Introductionmentioning
confidence: 99%